PENGEMBANGAN APLIKASI ANDROID BERUPA WORKBOOK FISIKA SEBAGAI PENDUKUNG MOBILE LEARNING UNTUK SISWA SMA - Widyanirmala Widyanirmala; I Made Astra; Hadi Nasbey; Fauzi Bakri; Ghina A. I.; Nur Azizah; Aditya Nugraha; Ruhiyat Rizki P (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
This research is to develop physics workbook with Android OS as mobile learning, an alternative learning for students. In addition to increase student interest, application development is also built to make students understand concepts through a workbook. Learning materials are limited to the theory of special relativity for third grade in Senior High School. In this research, the used method is research and development. The validation results show that the material of workbook is valid at 87.50%, while the media is valid at 84.25%, the empirical test of physics teacher result is valid at 78.49%, and students test result is valid at 79.23%. Thus it can be concluded that the physics workbook has already qualified as instructional media support mobile learning for Senior High School students. Keywords: Android, Workbook, Mobile Learning, Theory of Special Relativity.